"Isn't That a Girl Problem?": Boys, Bodies, and the Discourse of Denial. Issue 2 (1st December 2021) - Kehler, Michael; Borduas, Chris
Abstract: Revisions to Health and Physical Education (HPE) curriculums across Canada have prompted a conservative response denouncing the explicit and robust language used to address sexualities and young bodies. In this paper, we question the (in)visibility of male bodies and a prevailing discourse of denial, while situating the discussion alongside an evolving Canadian curriculum. Drawing on a national study, we examine narratives of adolescent boys to demonstrate how they make sense of locker-room interactions and bodily negotiations among their male peers. We introduce a discourse of denial to illustrate the ways in which adolescent male bodies and body image issues specifically have been misunderstood as a "girl problem" in schools. We argue that a limiting narrative of male bodies ignores the marginalization of boys facing shaming and homophobia in schools. We conclude by calling for a (re)consideration of male bodily practices while proposing changes that would more fully acknowledge adolescent male bodies in schools.